Environmental and climate changes and their effects on the agricultural sector in Iraq - Ahmed Shams Al-Din*, Naba’h; Nema Ali, Sabah (Journal of Economics and Administrative Sciences, 2024)
Purpose: The objective of this study was to aims to highlight the economic impacts of environmental and climate changes on both developed and developing countries, with a specific focus on Iraq's agricultural sectorTheoretical framework: The research dealt with environmental and climate changes and their effects on the agricultural sector in Iraq. The research problem revolves around the economic challenges facing Iraq, which revolve around the challenges of environmental and climate change, which exacerbate the problem of desertification, drought, and lack of water resources.Design/methodology/approach: The researcher adopted the deductive approach and the analytical descriptive approach to study environmental and climate changes as experiences for selected countries in order to reach analyzes and conclusions related to them. The period (2004-2022) was chosen because this period witnessed confrontation with environmental and climate changes and the worsening of carbon emissions, global warming, desertification, and drought in Many countries of the world, including Iraq.Findings: Environmental and climatic changes have a direct impact on the agricultural sector in Iraq, particularly amidst the challenges facing the global economy and food security. These changes pose an increasing threat to agricultural sectors worldwide, including in developing and Arab countries.Research, Practical & Social implications: We propose a future research agenda and highlight environmental and climate changes and their impacts on the agricultural sector in Iraq.Originality/value: The results indicate that the number of publications that addressed the impacts of environmental and climate change and their impacts on the agricultural sector.